Weapons of the rich strategic action of private entrepreneurs in contemporary China - Heberer, Thomas 1947-; Schubert, Gunter 1963- (World Scientific, 2020)
"This book provides a fresh perspective on the political agency of private entrepreneurs in contemporary China. Most Chinese scholarship describes this group as being politically acquiescent due to systematic co-optation by the party state. This book, however, argues that private entrepreneurs should be understood, and analytically conceptualized, as a 'strategic group' that makes use of different formal and informal channels to safeguard and expand its interests, though so far it has not challenged the current regime. State-business relations in contemporary China should thus be understood not in terms of mere clientelism, but as a dynamic symbiosis in which private entrepreneurs contribute substantially to policy and institutional change. This book is based on several years of comparative empirical fieldwork across China. With its rich and unique qualitative data and insights, this volume contributes significantly to our understanding of the political behaviour and impact of private entrepreneurs in contemporary China."
Includes bibliographical references and index
Keywords: Unternehmerverhalten; Privatunternehmen; Strategisches Management; Privatwirtschaft; China; Entrepreneurship / (DE-627)091396670 / (DE-STW)27358-1; Privatwirtschaft / (DE-627)091384354 / (DE-STW)12064-0; Privatisierung / (DE-627)091384303 / (DE-STW)10979-3; Strategisches Management / (DE-627)091393116 / (DE-STW)18029-0; China / (DE-627)091353777 / (DE-STW)17565-2; Entrepreneurship / China; Businesspeople / China; Privatization / China